Activities of daily living, instrumental activities for daily living and predictors of functional capacity of older men in Jamaica - Bourne, Paul Andrew (Medknow Publications & Media Pvt Ltd, 2009)
BACKGROUND: An extensive search of the literature found no studies that have examined functional capacity [Activities of Daily Living (ADL) and Instrumental Activities for Daily Living (I) ADL)] of Jamaican older men as well as factors that determine their functional capacity. AIMS: The current study examines 1) ADL, 2) (I) ADL), 3) self-reported health status, 4) functional capacity, and 5) factors that determine functional capacity of older men. METHODS AND METHOD: Stratified multistage probability sampling technique was used to draw a sample of 2,000 55+ year men. A132-item questionnaire was used to collect the data. Descriptive statistics provide background information on the sample, cross tabulations were used to examine non-metric variables and logistic regression provides a model of predictors of functional capacity. RESULT: Fifty-five percent of sample indicated good current health status. Four percent was mostly satisfied with life; 21.7% had moderate dependence; 77.1% had high dependence (i.e. independence); 1.2% had low dependence; 21.9% were ages 75 years and older; 35.6% were ages 65 to 74 years and 42.6% reported ages 55 to 64 years. Functional capacity can be determined by church attendance (β=0.245; 95% CI: 0.264, 1.291); social support (β=0.129; 95% CI: 0.129, 0.258), area of residence (β=-0.060; 95% CI: -0.427, -0.061) and lastly by age of respondents. CONCLUSION: Ageing in explains deterioration in their (I) ADL, suggesting the challenges of ageing men's independence. More rural men were rarely satisfied with life; but more of them had a greater functional capacity than urban men. Depression was found to negatively relate to functional capacity, and church attendees had a greater functional status than non-attendees.